ACTR-60. A PHASE 2, HISTORICALLY CONTROLLED STUDY TESTING THE EFFICACY OF TTFIELDS WITH ADJUVANT TEMOZOLOMIDE IN HIGH-RISK WHO GRADE II AND III ASTROCYTOMAS (FORWARD). (11th November 2019) - Tran, David; Ghiaseddin, Ashley; Allen, Anne
Abstract: BACKGROUND: A long-standing observation in neuro-oncology concerns a group of patients with WHO Grade II and III gliomas expressing isolated hTERT promoter mutations, which exhibit indolent histological features but are highly aggressive and resistant to standard chemoradiation therapy. These patients show an overall survival rate similar to glioblastoma WHO Grade IV, necessitating new treatment options. This represents the first study of its kind testing novel treatment for this rare subgroup of lower grade gliomas with high-risk cytogenetics. METHODS: This Phase 2, single arm, multicenter open label study [NCT03906448] will enroll 100 adult patients with newly diagnosed WHO grade II and III astrocytoma without IDH mutations and 1p/19q codeletions and with isolated hTERT promoter mutations who have completed standard radiotherapy with concurrent temozolomide, followed by adjuvant temozolomide for 12 cycles in combination with 24 months of TTFields therapy. The primary endpoint is overall survival compared to historical controls. Secondary endpoints are safety, quality of life, and progression free survival. Correlative studies will examine the effect of TTFields on intratumoral immune microenvironment and the role of electric field distribution on disease control and outcomes. Sample size was based on improvement in median OS versus historical controls (N=59; median survival 22 months). Improvements in median overall survival was based on a one-sided Wald test of the Weibull regression coefficient (H0: beta=0, alpha=0.05). A consortium of 15 institutions across the US will participate, with the first enrollment May 2019. Total accrual of 100 is planned over 36 months. The survival results and the correlative studies are designed to provide new insights for future therapeutic development for these patients.